A decade of colonization: the spread of the Asian tiger mosquito in Pennsylvania and implications for disease risk. Issue 1 (June 2017) - Taber, Eric D.; Hutchinson, Michael L.; Smithwick, Erica A.H.; Blanford, Justine I.
ABSTRACT: In recent decades, the Asian tiger mosquito expanded its geographic range throughout the northeastern United States, including Pennsylvania. The establishment of Aedes albopictus in novel areas raises significant public health concerns, since this species is a highly competent vector of several arboviruses, including chikungunya, West Nile, and dengue. In this study, we used geographic information systems (GIS) to examine a decade of colonization by Ae. albopictus throughout Pennsylvania between 2001 and 2010. We examined the spatial and temporal distribution of Ae. albopictus using spatial statistical analysis and examined the risk of dengue virus transmission using a model that captures the probability of transmission. Our findings show that since 2001, the Ae. albopictus population in Pennsylvania has increased, becoming established and expanding in range throughout much of the state. Since 2010, imported cases of dengue fever have been recorded in Pennsylvania. Imported cases of dengue, in combination with summer temperatures conducive for virus transmission, raise the risk of local disease transmission.